Kualitas Pelayanan Publik di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonosobo Tahun 2022 - Saputri, Rasta Oki Hudi; Muttaqin, Azmi (JURNAL LANSKAP POLITIK, 2023)
This paper aims to determine the implementation of the quality of public services at the Wonosobo District Population and Civil Registry Office in 2022. Using qualitative research methods and theory according to Valerie A.Zeithaml, A.Parasuraman, and Leorard L.Berry with ten sub-indicators, namely: Physical facilities (tangible), reliability (reliability), responsiveness (responsiveness), competence (competency), governance (courtesy), credibility (credibiliy), security (security), access (access), communication (communication), and attention to customers ( understanding the customer). Based on the results of research and data analysis that has been carried out by researchers and the elaboration of the theory used, it can be concluded that the quality of public services at the Population and Civil Registration Office of Wonosobo Regency is categorized as good.